Tikanga rua: Bicultural spatial governance in Aotearoa New Zealand - Dionisio, Rita; Macfarlane, Angus Hikairo (New Zealand Geographer, 2021)
This editorial introduction outlines the political and intellectual territory for a Special Issue on Tikanga rua: bicultural spatial governance in Aotearoa New Zealand. The term ‘spatial governance’ refers to deliberative systems with an impact on social and spatial outcomes, including environmental management, town planning, urban design and city-making. Authentic tikanga rua bicultural spatial governance delivers processes and outcomes aligned with the perspectives, values and knowledge of both tangata whenua (people of the land) and tangata Tiriti (people of the Treaty). The research discussed in the Special Issue traverses multiple geographies and contexts and demonstrates the manifold possibilities for biculturalism in contemporary spatial governance. This introduction summarises the contents of each of the substantive papers and provides a Māori-English glossary to assist readers with the key terms used within the issue.
Keywords: bicultural; governance; tikanga | indigenous law

Maori sustainable development in the 21st century: The importance of Maori values, strategic planning and information systems - Harmsworth, Garth; Barclay-Kerr, Kim; Reedy, Tamati (He Puna Korero: Journal of Maori & Pacific Development, 2002)
Keywords: autonomy; economic development; governance; rangatiratanga; self-determination

Shaky Foundations: The fundamental flaw at the heart of a “model” treaty involving New Zealand and the Indigenous Māori community - Charters, Claire; Whare, Tracey (World Policy Journal, 2017)
In 1840, English officials on behalf of the British crown signed the Treaty of Waitangi—also known as Te Tiriti o Waitangi—with the Indigenous Māori population, affirming Māori sovereignty and guaranteeing their collective rights to the country’s land and resources. Since the 1700s, English settlers had been arriving in Aotearoa (the Māori name for New Zealand) to capitalize on the seal and whale trade. As the number of settlers increased, reports flowed back to Britain of general lawlessness and dubious private land deals, and the crown was forced to consider how best to control its citizens. A treaty with the Māori, officials decided, was the way to do so. The agreement, which established the basis for the relationship between the Māori and the British, is commonly cited as a shining example of how a treaty can recognize and protect Indigenous peoples’ rights by curtailing the reach of the state. But does te Tiriti live up to its sterling reputation? The answer, of course, is complicated.
Keywords: colonisation; crown policy; governance; kāwanatanga; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Navigating towards marine co-management with Indigenous communities on-board the Waka-Taurua - Maxwell, Kimberley H.; Ratana, Kelly; Davies, Kathryn K.; Taiapa, Caine; Awatere, Shaun (Marine Policy, 2020)
Developing equitable marine management systems that recognise Indigenous worldviews, values, and practices, alongside international initiatives such as Ecosystem-Based Management (EBM) are paramount in countries which aim to recognise Indigenous rights. This is the case for New Zealand (NZ) where Indigenous-Māori rights to partner with the Government for the purpose of environmental management were guaranteed under the Treaty of Waitangi, 1840, and subsequent Acts (e.g. Resource Management Act, 1991). Our aim was to explore how both Indigenous-Māori and NZ societal values can be integrated into a marine co-management decision-making framework. Here we describe the Waka-Taurua (double-canoe) framework, and how it can be applied in developing a NZ marine management system (NZ-MMS), which includes both kaitiakitanga (a Māori concept of reciprocal care between Indigenous-Māori people and their territorial environment), and EBM, equitably. We argue that the Waka-Taurua framework can improve how marine co-management systems are developed by facilitating a more structured and equitable discussion of both Indigenous-Māori and broader societal worldviews, values, and practices.
Keywords: environmental management; governance; kaitiakitanga; kāwanatanga; water management

Using mātauranga Māori to inform freshwater management - Harmsworth, Garth; Awatere, S.; Pauling, C. (Landcare Research Policy Brief, 2013)
Keywords: co-governance; environment; governance; hapū; iwi; kāwanatanga; local government; water management

Integrating Indigenous Knowledge and Freshwater Management: An Aotearoa/New Zealand Case Study - Hudson, Maui; Watene-Rawiri, Erina; Robb, Mahuru; Collier, Kevin; Awatere, Shaun; Harmsworth, Garth; Henry, Jacqueline; Quinn, John; Death, Russell; Hamilton, David; Maru, John (The International Journal of Science in Society, 2016)
Keywords: governance; iwi; kāwanatanga; local government; treaty settlements; water management

The relevance of Te Tiriti o Waitangi in the COVID-19 era - Charters, Claire (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
Keywords: covid-19; governance; rangatiratanga; tiriti o waitangi/treaty of waitangi

Census 2018 and Implications for Māori - Kukutai, Tahu; Cormack, Donna (New Zealand Population Review, 2018)
The population census is a universal tool of governance but has come under increasing pressure as governments look to reduce costs, gain efficiencies and counter declining response rates. In Aotearoa New Zealand, the census transformation strategy has a short-term focus on modernising the census and a long-term vision of a fully administrative census. The digital-first 2018 Census was an ambitious step towards modernisation but there are growing concerns that it may fail to deliver high-quality data, particularly for Māori and iwi. This research note considers the implications of lower response rates and reflects on the steps that might be taken to retain the trust and confidence of Māori in the census, including possibilities for Māori data governance across the official statistics system.
Keywords: census; data collection; governance; methodology; population; population studies; sovereignty; transformation